'Have you insured yourself in any way?' Salespersons' mapping questions and their follow-ups in insurance sales negotiations - Niemi, Jarkko; Heinonen, Pilvi (SAGE PUBLICATIONS INC, 2026)
This study examines how insurance salespeople employ a mapping question to promote life insurance as an additional service to their customers. The mapping question serves a double function, asking about the customer's situation and creating a context in which transaction-related negotiation is projected to occur. Applying conversation analysis to study video-recorded insurance meetings in Finland, we explore how the mapping question is designed according to the customer's estimated fit with the target group criteria and their assumed level of understanding of life insurance. We also discuss the trajectories of the negotiation after the customer's response that expresses interest, conveys hesitation, or rejects the offer. It was found that only a customer's justified blocking response forestalls further life insurance promotion. The study contributes to the research on questions as agenda-driving actions in institutional interaction and to the literature on question-answer sequences in service encounters.